A Survey of Learning Media Utilization in Elementary School Survei Pemanfaatan Media Pembelajaran di Sekolah Dasar - Sudi Pratikno, Ahmad; Sumantri, Sumantri (Al-Mudarris: Journal Of Education, 2023)
The principle objective of this research, first was to survey the need of learning media in four public schools which consist of 55 samples, second was to engage learning media which contain of environmental awareness in primary schools. This research used documentations, observations, and in-depth interviews to collect data. The data analysis used quantitative and descriptive analysis. The findings reveal that learning media in which frequently used by teachers as follows laptop and LCD (31,25%), books (62,5%), and others (6,25%), while learning media which expected or needed by students were: reality (62,5%) and multimedia (37,5%). Findings suggest that teacher might provide reality and multimedia as a learning media which contain interactive material to the students.